Social Capital, Labour Market Status and Wages: Some Evidence from Spain. - Caparrós-Ruiz, Antonio (Emerald, 2020)
This article analyses the social capital’s influence on the Spanish labour market. In particular, this study examines to what extent the social capital increases the likelihood of being employed, taking into account different labour market status, and diverse dimensions of the social capital. Focusing on wage earners, it is also analysed whether network structures in Spain influence on the wage earnings. The methodology applied to analyse the labour market status is a multinomial logit model. For the analysis of wages, it is specified a wage model with sample selection bias. In both cases, social capital indicators are included as regressors. The results show that social participation exerts a positive influence on the probability of being self-employed, and lowers the likelihood of being unemployed. Moreover, it is verified that the interaction with family members or close friends influences positively on wages. Further research should emphasise how employers assess the workers’ competences associated with the social capital. The findings provide knowledge to policymakers useful to increase the role of social participation in the labour market. The importance of social network as an instrument for the job search must be enhanced. This article overcomes some drawbacks associated with the analysis of social capital from an aggregate perspective. Furthermore, social capital indicators are obtained using the Categorical Principal Components Analysis (CATPCA), which is unprecedented in the economic literature.
Keywords: Mercado de trabajo - Aspectos sociales; Labour market outcomes; CATPCA; Social capital